Post Lumber Punction Headache in Pediatric Cases - Özlem Yayıcı Köken; Ayşegül Danış; Ülkühan Öztoprak; Ayşe Aksoy; Deniz Yuksel (Van Tıp Dergisi, 2021)
INTRODUCTION: Lumbar puncture (LP) is a frequently used as a diagnostical and treatment tool in the practice of pediatric neurology. Headache associated with LP directly effects the physician and the family concerning patient comfort in a negative manner. The aim of this study is to evaluate and present to the literature, the clinical features, treatment strategies and prognoses of 8 cases with postdural puncture headache (PDPH). METHODS: Eight cases with clinical findings who underwent LP for various reasons and diagnosed as PDPH in the last three years at the pediatric neurology department of SBU, Ankara Dr. Sami Ulus Training and Research Hospital were retrospectively evaluated. RESULTS: The patients' mean age were 12.2 and 4 (50%) of them were male. Headache started within first 4 hours in 5 patients while 3 patients reported pain within the first hour after LP. Headaches, which were accompanied by a sensation of pressure and/or throbbing were located occipitally in 2 (25%), frontally in 2 (25%), frontotemporally in 1 (12,5%), bitemporally in 1 (12,5%) patient while it extended to the neck in 2 (25%) patients. All patients were supported with increased liquid intake, absolute bed rest, feet elevation, intravenous hydration and paracetamol while 6 patients were given oral caffeine. The pain gradually disappeared in an average of 2,7 days while it took relatively longer in 2 patients who were overweight and obese. DISCUSSION AND CONCLUSION: Although PDPH is a frightening situation by both the clinician, patient and parents; it can usually be controlled with supportive treatment and has a benign course.